2020
DOI: 10.21608/edj.2020.77496
|View full text |Cite
|
Sign up to set email alerts
|

Audio-Visual Distraction Effect on Heart Rate in Children during Dental Treatment, A Randomized Clinical Trial

Abstract: Background: Dental anxiety is one of the causes of avoiding dental visits in children and is associated with physiological body reactions as increased heart rate. Different behavior management techniques have been used to reduce dental anxiety among them are Tell-show-do technique and audiovisual (AV) distraction. Aim:To determine the effect of audiovisual distraction on heart rate during dental treatment in children. Subjects and methods:Forty-two patients requiring pulp therapy were randomly allocated to eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Some studies have shown that audiovisual distraction (e.g., cartoons, music, kaleidoscope) before or during medical procedures in young children can improve their behavior and reduce anxiety levels. 3,6,[7][8][9][10][11][15][16][17] Our study observed a significant reduction in anxiety levels measured using VAS-A score after intervention during the echocardiography procedure. The proportion of subjects with VAS-A scores in the "calm and relaxed" and "mild anxiety" ranges were increased post-audiovisual distraction, compared to higher anxiety levels pre-intervention; these results are consistent with those of several studies that have reported that audiovisual distraction can reduce pain.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Some studies have shown that audiovisual distraction (e.g., cartoons, music, kaleidoscope) before or during medical procedures in young children can improve their behavior and reduce anxiety levels. 3,6,[7][8][9][10][11][15][16][17] Our study observed a significant reduction in anxiety levels measured using VAS-A score after intervention during the echocardiography procedure. The proportion of subjects with VAS-A scores in the "calm and relaxed" and "mild anxiety" ranges were increased post-audiovisual distraction, compared to higher anxiety levels pre-intervention; these results are consistent with those of several studies that have reported that audiovisual distraction can reduce pain.…”
Section: Discussionmentioning
confidence: 87%
“…The proportion of subjects with VAS-A scores in the "calm and relaxed" and "mild anxiety" ranges were increased post-audiovisual distraction, compared to higher anxiety levels pre-intervention; these results are consistent with those of several studies that have reported that audiovisual distraction can reduce pain. 3,6,[7][8][9][10][11][15][16][17] Preschool children commonly enjoy watching animated cartoons, and they become deeply engaged to the point of being oblivious to their surroundings, thereby ignoring verbal and tactile stimuli caused by medical procedures. All children in our study were familiar with audiovisual stimuli from their devices, such as mobile phones and/or television, which may have helped reduce their anxiety during the echocardiography procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency and percentage values for ease of handling patients in different groups are presented in Table (2). Regarding the ease of handling patients during extraction, there was a significant difference between both groups (p<0.001), with the majority of the cases in group A [15(88.2%)] having" strongly agree" scores and most of the cases in group B [9(52.9%)] being" Neutral".…”
Section: -Ease Of Handling Patientsmentioning
confidence: 99%
“…Adel Zakhary et al demonstrated the beneficial effects of rehabilitation programs along with oral education in reducing dental anxiety (13). In another study, Zhang also showed that audiovisual distraction can effectively reduce dental anxiety among children (14).…”
Section: Introductionmentioning
confidence: 99%